The Use of Vocabulary Learning Strategies by Music and Dance Learners of the State University of Surabaya - Lolita, Yuri; Fauzia, Nur (JET ADI BUANA, 2018)
This study was conducted to examine the use of vocabulary learning strategies (VLSs) by Music and Dance students as well as the impact of gender and grade levels on the use of learning strategies. A five Likert scale questionnaire, consisting of 36 items was classified under four strategy categories was administrated to 466 participants from the State University of Surabaya. There are male and female. The Statistical Package of Social Science (SPSS, version 20) was used to analyze the obtained data. The results of the descriptive statistics showed that The State university of Surabaya students were medium strategy users. The study also found that the cognitive strategies were the most popular strategies among the learners. Social strategies were found to be the least preferred strategies. The results of the t-test showed that in general, the scores of female learners regarding the use of VLSs were slightly higher than male learners. Moreover, Music learners were found to be more strategy users than Dance learners. The results of ANOVA revealed significant differences regarding the use of VLSs and grade levels. Keywords: Vocabulary learning strategies, Music/Dance learners